Biodisponibilização do fósforo, incremento de energia e digestibilidade de nutrientes na dieta de frangos de corte contendo exoenzima fitase - Litz, Fernanda Heloisa (2013)
This study aimed to evaluate the effect of the use of phytase exoenzyme and other mineral sources on the bioavailability of phosphorus , increased dietary energy and nutrient digestibility . The treatments were : sorghum with inorganic phosphate ( SFB ) , maize with inorganic phosphate ( MFB ) , sorghum meal, meat and bone meal ( SFco ) , sorghum with phytase ( SFV ) and without energy recovery and amino acids ( SFNV ) . 1400 birds were for performance reviews , which were determined feed intake , body weight , feed conversion real and traditional and viability . For the analysis of digestibility at 15 days were used 80 birds , which were subjected to total collection , now for carcass composition and mineralization of tibia were used 6 birds per treatment , where we proceeded to determine the dry matter , crude protein , ether extract , ash , gross energy housing , and calcium and phosphorus of tibia and carcass. Data were subjected to analysis of variance and means were compared by Tukey test at 5 % and viability Kruskal-Wallis test . There were no statistical differences in performance at 7 days of age and only 14 live weight was lower for the MFB , however at 42 days , body weight was greater for the SFB compared to the MFB . Digestibility at 15 days there was no statistical difference. For carcass composition, the SFV showed higher percentage of ether extract. The percentage of calcium MFB FCS and were lower compared with the SFNV and equal to SFco and SFV , and the phosphorus content of the SFV and SFNV showed higher values. The exogenous phytase enzyme is able to hydrolyze phytate and release phosphorus from vegetable source for assimilation by animals , thus acting as a substitute for vegetable sources of phosphorus.